Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Nucleobases in molecular recognition: molecular adducts of adenine and cytosine with COOH functional groups - Perumal, Sathiamurthi; Suresh, E.; Pedireddi, V. R. (Angewandte Chemie International Edition, 2005)
Keywords: carboxylic acids; hydrogen bonds; molecular recognition; nucleobases; supramolecular chemistry

Structural rationalisation of co-crystals formed between trithiocyanuric acid and molecules containing hydrogen bonding functionality - Ahn, Sung-Hoon; PrakashaReddy, J.; Kariuki, B. M.; Chatterjee, S.; Ranganathan, A.; Pedireddi, V. R.; Rao, C. N. R.; Harris, Kenneth D. M. (Chemistry - A European Journal, 2005)
Crystallisation of trithiocyanuric acid (TTCA) from various organic solvents that have hydrogen bonding capability (acetone, 2-butanone, dimethylformamide, dimethyl sulfoxide, methanol and acetonitrile) leads to the formation of co-crystals in which the solvent molecules are incorporated together with TTCA in the crystal structure. Structure determination by single-crystal X-ray diffraction reveals that these co-crystals can be classified into different groups depending upon the topological arrangement of the TTCA molecules in the crystal structure. Thus, three different types of single-tape arrangements of TTCA molecules and one type of double-tape arrangement of TTCA molecules are identified. In all co-crystals, hydrogen-bonding interactions are formed through the involvement of N-H bonds of TTCA molecules in these tapes and the other molecule in the co-crystal. Detailed rationalisation of the structural properties of these co-crystals is presented.
Symposium on Chemistry-A European Conference - Stimulating Concepts in Chemistry, Inst Sci Ingenierie Supramoleculaires, Strasbourg, FRANCE, APR 15, 2005
Keywords: crystal engineering; hydrogen bonds; nitrogen heterocycles; structure elucidation

Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

pK(a)-Directed host-guest assemblies: rational analysis of molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine with various aliphatic dicarboxylic acids - Delori, Amit; Suresh, Eringathodi; Pedireddi, V. R. (Chemistry-A European Journal, 2008)
Molecular adducts of 2,4-diamino-6-methyl-1,3,5-triazine (1) have been prepared with various aliphatic dicarboxylic acids. The molecular complexes (1a-1i) thus formed by co-crystallizing 1 with oxalic, malonic, succinic, fumaric, acetylene dicarboxylic, glutaric, thiodiglycolic, diglycolic, and adipic acids have been found to give two types of host-guest assemblies that have voids or channels in a three-dimensional arrangement. The different types of host-guest arrangement appear to result from differences in the acidity of the dicarboxylic acids, that is, acids with pK(a) < 3.0 give host networks that consist of 1 and the corresponding acid with water or solvent molecules of crystallization present as guests, whereas acids with pK(a) > 3.0 exist as guests in voids in a host network formed by 1. The former arrangement is observed in adducts 1a, 1b, 1c, and 1h and the latter arrangement is found in adducts 1c, 1d, 1f, 1g and 1i.
Keywords: dicarboxylic acids; host-guest systems; hydrogen bonds; molecular recognition; supramolecular chemistry

C-H center dot center dot center dot N hydrogen bonds mediated solid state structures of 2,2 `-bis (4-pyridylsulfanylmethyl)-1,1 `-biphenyl and 9-(4-pyridylsulfanyl)phenanthrene - Upadhye, Ketaki; PrakashaReddy, J.; Pedireddi, V. R. (Journal of Molecular Structure, 2009)
Solid state structure elucidation of sulfanyl ligands, 2,2'-bis(4-pyridylsulfany[methyl)-1,1'-biphenyl, L(1) and 9-(4-pyridylsulfanyl)plienanthrene, L(2) are reported. In the structures L(1) and L(2), the molecules are self-assembled through C-H center dot center dot center dot N hydrogen bonds, yielding ensembles of cyclic and helical networks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonds; noncovalent interactions; Supramolecular assemblies

Enhancement of chemical stability and crystallinity in porphyrin-containing covalent organic frameworks by intramolecular hydrogen bonds - Kandambeth, Sharath; Shinde, Digambar Balaji; Panda, Manas K.; Lukose, Binit; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2013)
Keywords: covalent organic frameworks; hydrogen bonds; mesoporous materials; porphyrinoids; tautomerism

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs